Promotion Management Through A Merit System In The Education And Training Personnel Agency, Mamasa Regency, West Sulawesi Province (Institut Pemerintahan Dalam Negeri, 2022)
Job promotion is one of the activities of the State Civil Apparatus Management. It is implemented through a merit system to obtain employees with qualifications, competencies, and performance fairly and equitably to occupy a higher position. This study aimed to identify and analyze job promotion management through the merit system at the Education and Training Personnel Agency, commonly known as Badan Kepegawaian Pendidikan dan Pelatihan (BKPP) in Mamasa Regency, West Sulawesi Province. A qualitative descriptive method was used to analyze promotion management with aspects such as (1) planning, (2) organizing, (3) implementation, and (4) supervision. The results showed that job promotion management through the merit system has been running well regarding organization and supervision, but there are obstacles in the planning and implementation aspects. Therefore, it is necessary to make a Regent's or Regional Regulation based on local considerations. There is also a need for consistency in public information disclosure in job promotions that use competency tests.